PREPARATION OF NATIONAL TEAMS FOR MAIN COMPETITIONS - Talipjanov A. I. (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides an overview of generally recognized principles for drafting training to prepare a national team for competitions.